SIKAP SISWA TERHADAP KEPEDULIAN LINGKUNGAN DI SMPN 3 BANJARMASIN TAHUN AJARAN 2014/2015 - Heny Muranti; Ellyn Normelani; Karunia Puji Hastuti (JPG (Jurnal Pendidikan Geografi), 2015)
This research entitles “The Student’s Attitude through the Environment at SMPN 3 Banjarmasin Academic Year 2014/2015. The purpose of this research is to know the student’s attitude through the environment at SMP 3 Banjarmasin.The research method  that used in this research is quantitative research. The population in this research isthe students at SMP 3 Banjarmasin that consist of 686 students. Thesamples of this research are 247 students, chosen by random sampling system. The technique for gained data is based on primer and seconder. The primer data gained from the observation and questionnaire, while the seconder data gained from the document study. The process of collecting data was done by editing, coding, and tabulation. The percentage analysis was used to describe the data analysis. The result of this research showed that the students has care attitude thoroughly about environment by presentation 89,81 %, it means most students care about the environment by not throwing garbage anywhere, always keep cleanliness and conservation of school’s environment. The hypothesis in this research is the student’s attitude to care about the environment at State Junior High School 3 Banjarmasin in 2014-2015 academic year is told most of them care, and based on the result of research which is done, so the hypothesis is rejected. Key words: Attitude, Students, Attention to the environment